Optimization of Learning of The Qur’an Hadith Through The Use of Google Classroom in The Covid-19 Emergency - Fatihatul Nur Choiriyah; Afif Kholisun Nashoih (SCHOOLAR: Social and Literature Study in Education, 2023)
The Covid-19 pandemic has had a significant impact in the field of education, namely the implementation of distance learning to limit the spread of the virus. In this condition, the use of e-learning becomes an absolute obligation that must be applied in the learning process. The purpose of this study was to determine the effectiveness of learning Al-Qur'an Hadith through Google Classroom-based E-learning media during the covid-19 pandemic. This study uses a qualitative descriptive method, this is because the object under study is a complex interaction process, namely the optimization of Al-Qur'an Hadith learning through google classroom during the covid-19 pandemic at MI Al-hikmah. The instrument used in this study was direct observation in the field and accompanied by a questionnaire conducted by researchers to the teacher and students. The results of this study indicate that the google classroom application is very appropriate and efficient for the online learning process because it is not bound by time limits or official lesson hours in collecting assignments, distributing assignments, and assessing student assignments.